A two-stage multi-criteria analysis method for planning renewable energy use and carbon saving. (15th May 2020) - Ahmed, Asam; Sutrisno, Setiadi Wicaksono; You, Siming
Abstract: Renewable energy use is critical for achieving climate change goals. It is essential to understand necessary to the priority, capacity, and number of units of renewable energy systems for generation planning. Multi-criteria analysis methods serve as an effective tool for planning renewable energy generation. In this work, a two-stage multi-criteria analysis method was developed to identify the priority and capacities, as well as the numbers of units of renewable energy technologies. Technical (capacity factor and power density), economic (benefit-to-cost ratio), and environmental (carbon dioxide equivalent emission) criteria were considered. The method was applied to plan Glasgow's renewable energy use. It was found that the planned renewable energy use configuration consists of 255 units of wind turbines (3.6 MW each), 23, 497 units of solar photovoltaic panels (11 kW each), 2 units of biomass combustion systems (2 MW each), and 3382 units of ground source heat pumps (22.5 kW each) corresponding to an annual carbon footprint of 109, 629 tonnes carbon dioxide equivalent. Sensitivity analysis was also conducted to assess the impacts of weightings in technical, economic, and environmental criteria on the decision in the configuration of renewable energy use. Highlights: A two-stage multi-criteria analysis tool developed for renewable energy planning. Technical, economic, and environmental criteria considered. Economically, wind turbines and bioenergy prioritized for electricity and heat production. The plan has 255 wind turbines, 23, 497 PV panels, 2 bioenergy units, and 3382 GSHPs. The plan has an annual carbon footprint of 109, 629 ton CO2-eq .